The Implementation Of Character Education In Reducing Violence In Early Childhood At Paud An-Nur Village Ndano Na'e - Suryani; Hendra; Muslimin (UNIB Press, 2025)
The research team at Paud An-Nur, Ndano Na'e Village sought to find out how character education can reduce early childhood violence. Character education has the potential to reduce violence against young children in Paud An-Nur, Ndano Na'e Village, but this study also identifies variables that can hinder or facilitate its implementation. This study aims to analyse the implementation of character education in reducing violence in Early Childhood at PAUD An-Nur, Ndano Na'e Village and to analyse the supporting and inhibiting factors in the implementation of character education in reducing violence in Early Childhood at PAUD An-Nur, Ndano Na'e Village. This research uses qualitative research methods. Based on the findings of this study, character education has successfully reduced the rate of violence against early childhood in PAUD An-Nur, Ndano Na'e Village. The programme promotes the development of important character traits including empathy, discipline and cooperation through an integrated strategy involving parents, children and educators. As a result, the rate of physical violence between children has decreased dramatically. The success of the programme depends on the cooperation of teachers, parents and the community. The character education programme at PAUD An-Nur can serve as an example for other PAUD schools by fostering a violence-free atmosphere if it receives consistent and sustained support. Many obstacles were faced, but one school managed to overcome them by finding ways to involve parents more and help fund the character education programme. This programme can serve as an example for other ECD institutions by actively collaborating and continuously working towards a violence-free learning environment..